Case studies in financial counseling - Bagwell, Dorothy C.; Harris, Steven M. ([United Kingdom] : Bagwell-Harris, 2005)
A case study that discuss regarding the financial, how to planning, family counseling, our expenses, how to handle it, and so on
Title from title screen
Keywords: Finance, personal -- Case studies; Counseling -- Case studies